PEMBANGUNAN BERBASIS MASYARAKAT DALAM UPAYA PENGEMBANGAN BANK SAMPAH KENCANA, KELURAHAN CANDIREJO, KECAMATAN UNGARAN BARAT, KABUPATEN SEMARANG - Maulina Erza Safitri; Amni Zarkasyi Rahman; Retna Hanani (Journal of Public Policy and Management Review, 2023)
Waste Bank is one of the efforts to reduce waste generation and as a community-based development activity. The purpose of this study was to analyze the management of a community-based waste bank at the Kencana Waste Bank, Candirejo Village, Ungaran Barat District, Semarang Regency using a community-based development cycle. This research method is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results showed that the community-based waste bank management at the Kencana Waste Bank had been going well, although there were still some things that were lacking in implementation. Of the seven cycles, the cycle of Increasing Community Group Participation and the cycle of Growing Competence of Community Groups to Change is the best cycle because there are no obstacles. Recommendations that can be given are evaluating the mechanism for registering customers of the Kencana Waste Bank, continuing to carry out socialization, education and motivation regarding waste sorting, implementing 3Rs in daily life, the importance of doing good and correct waste management, and increasing community participation in joining the Bank. Waste Kencana and the need for additional human resources in the environmental conservation facilitator team at the Semarang Regency Environmental Service